Partnership-based governance and standardization of vocational teacher education in Ukraine - Deißinger, Thomas [Herausgeber]; Melnyk, Oksana [Herausgeber] (wbv Media GmbH & Co. KG, 2024)
"This publication addresses the pressing issues of vocational teacher education (VTE), focusing on institutional, organizational and governance aspects. Firstly, it summarizes the results of the four-year Erasmus+ capacity-building project "New Mechanisms of Partnership-based Governance and Standardization of Vocational Teacher Education in Ukraine" (PAGOSTE), funded by the European Education and Culture Executive Agency. The project's focus has been governance in VTE in Ukraine. Secondly, it goes beyond the narrow project context and explores challenges as well as good practices in VTE systems of other countries in and outside of Europe. Therefore, contributions from England, New Zealand, Australia, Italy, Germany, Austria and Switzerland complement the Ukrainian context and provide readers with a more comprehensive understanding of VTE systems." (Publisher, BIBB-Doku)
Keywords: P 3.2.3 Lehrer; S 4.3 Steuerung; S 2.4 Kooperation; I 2.2.2 Osteuropa; I 2.2.1 Westeuropa; I 2.3.5 Australien, Ozeanien; 370; Berufsschullehrer; Lehrerbildung; Governance; Kooperation; Standardisierung; Professionalisierung; Lebenslanges Lernen; Australien; Bundesrepublik Deutschland; Großbritannien; Neuseeland; Österreich; Schweiz; Ukraine